Introduction to Symposium on UN Recognition of the Human Right to a Healthy Environment - John H. Knox (AJIL Unbound, 2023)
In July 2022, the United Nations General Assembly adopted a resolution recognizing the human right to a clean, healthy, and sustainable environment. Its proponents hope that the resolution will catalyze further action, but many of the states voting for it expressed the view that it has no legal effect in itself. Will UN recognition of this right nevertheless change international law? If so, how? This symposium brings together the perspectives of six distinguished scholars on this question. Philip Alston and Carmen Gonzalez examine how recognition may change our understanding of human rights law; Hélène Tigroudja and Maria Antonia Tigre analyze its impact on the burgeoning environmental jurisprudence of the UN human rights treaty bodies and the Inter-American Court of Human Rights; Rosemary Mwanza explores how the right may affect parallel efforts to codify the crime of ecocide; and Louis Kotzé concludes by arguing that the right still falls short of the transformational shift necessary to recognize and protect the rights of nature and of future generations. Before describing their contributions in more detail, this introduction reviews the background of the resolution and describes its main provisions.